Frequency of CSF Rhinorrhoea in Patients Undergoing Endoscopic Transsphenoidal Surgery (ETSS) for Pituitary Macroadenoma - Sohaib Ali, Tauseef Ullah, Muhammad Ibrahim Afridi, Tabraiz Wali Shah, Shafiq Ur Rehman, Hanif Ur Rahman, Idris Khan, Muhammad Taimur Khan, Ehsan Sayyed (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Pituitary adenoma resection via the transsphenoidal approach (TSS)is a safe and common neurosurgical procedure that can be done both through microscopic and endoscopic methods. Objectives: The main objective of the study is to find the frequency of CSF rhinorrhoea in patients undergoing endoscopic transsphenoidal surgery (ETSS) for pituitary macroadenoma. Material and methods: The study data was collected from 1st Oct to 1st Nov 2022, in the departments of Neurosurgery of Hayatabad Medical complex, Khyber Teaching Hospital, Lady Reading Hospital, Peshawar. The data was collected through non-probability consecutive sampling technique. There were 315 patients which were included in the study. The surgical procedure is done under general anesthesia. All patient data was collected and a standardized form was filled by the attending surgeon caring for the patient. Importantly, the primary end points to be recorded were: (1) techniques of intraoperative cranium base reconstruction used, and (2) postoperative CSF rhinorrhoea biochemically confirmed and/or requiring intervention (CSF diversion and/or operative restoration). Results: Of the 315 consecutive patients diagnosed with pituitary adenomas, a total of 250 patients met the inclusion criteria and were included. The pathology included 187 (74.8%) non-functioning adenomas, 40 (16.0%) GH-secreting pituitary adenomas, 3 (1.2%) PRL-secreting pituitary adenomas, and 20 (8.0%) ACTH-secreting pituitary adenomas. There were 30 (12.0%) cases of microadenomas, 205 (82.0%) cases of macroadenomas, and 15 (6.0%) cases of giant adenomas. Intraoperative CSF leakages were determined throughout surgical procedure in eighty patients (32.0%). Postoperative CSF leaks occurred in 9 patients (3.6%), including seven patients with intraoperative CSF leaks. Practical implication: Practical implications of this study is: (1) easily find the CSF leakage (2) frequency of CSF rhinorrhoea in patients undergoing endoscopic transsphenoidal surgery Conclusion: It is concluded that macroadenoma ETSS surgery should be strictly monitored for post-operative CSF leakage and lumber drain is an effective prophylactic strategy. Keywords: Postoperative CSF Leakage, Pituitary Adenomas, ETSS, Surgery, Lumber